Assessment of the Impact of Zinc, Iron and Vitamin D Deficiencies on the Prevalence of Dermatological Disorders Among Females in Taiz-Yemen. - Mohammed, Aisha Yasser; Alariqi, Aya Waheeb; Alariqi, Ghofran Hani; Alwardi, Nada Mokhtar; Alwardi, Reem Fouad (University of Science and Technology, Sana’a, 2026)
Background: Micronutrient deficiencies, particularly zinc, iron, and vitamin D, are increasingly recognized as pivotal factors in the pathogenesis and exacerbation of various dermatological conditions. In Yemen, nutritional challenges among females may significantly contribute to skin morbidity. Objective: This study aimed to assess the impact of serum levels of zinc, iron, and vitamin D on the prevalence and severity of dermatological disorders among females in Taiz city, Yemen. Methodology: A descriptive cross-sectional study was conducted involving 47 female participants (30 patients with skin disorders and 17 healthy controls) aged 18–50 years. Clinical data were collected via structured questionnaires, and biochemical analyses were performed to measure Hemoglobin (Hb), Serum Iron, Serum Zinc, and Vitamin D levels. Statistical analysis was performed using SPSS (T-test and ANOVA) to determine the significance of correlations (P < 0.05). Results: The study revealed that 60% of the participants suffered from dermatological disorders. A significant reduction in serum iron levels was observed in patients compared to controls (92.47 ± 11.91 μg/dL vs. 76.75 ± 20.74 μg/dL, P=0.006). Vitamin D deficiency was prevalent among cases with a mean level of 24.70 ± 4.79 ng/mL. While serum zinc levels were lower in the patient group (58.47 ± 12.18 μg/dL) compared to controls (81.18 ± 10.81 μg/dL), showing a highly statistical significant (P<0.001). Regarding disease duration, a significant correlation was found between serum iron levels and the persistence of skin conditions (P=0.024). Conclusion: Deficiencies in zinc, iron and vitamin D are significantly associated with the prevalence of skin disorders among Yemeni females. These findings emphasize the necessity of integrating nutritional screening and supplementation into dermatological clinical practice to improve therapeutic outcomes.